2019
DOI: 10.1038/s41598-019-44626-0
|View full text |Cite
|
Sign up to set email alerts
|

Global geographic patterns of heterospecific pollen receipt help uncover potential ecological and evolutionary impacts across plant communities worldwide

Abstract: Species interactions are known to be key in driving patterns of biodiversity across the globe. Plant-plant interactions through heterospecific pollen (HP) transfer by their shared pollinators is common and has consequences for plant reproductive success and floral evolution, and thus has the potential to influence global patterns of biodiversity and plant community assembly. The literature on HP transfer is growing and it is therefore timely to review patterns and causes of among-species variation in HP receip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…Thus, this latter species could be expected to be more efficient at avoiding HP (see McLernon et al., ; Montgomery and Rathcke, ). A recent global analysis also showed that species with radial flowers receive higher HP loads compared to bilateral flowers (Arceo‐Gómez et al., ). In fact, in the present study, S. plumieri (bilateral flowers) received significantly less HP than C. edentula (radial flowers).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, this latter species could be expected to be more efficient at avoiding HP (see McLernon et al., ; Montgomery and Rathcke, ). A recent global analysis also showed that species with radial flowers receive higher HP loads compared to bilateral flowers (Arceo‐Gómez et al., ). In fact, in the present study, S. plumieri (bilateral flowers) received significantly less HP than C. edentula (radial flowers).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, in the present study, S. plumieri (bilateral flowers) received significantly less HP than C. edentula (radial flowers). Thus, because S. plumieri is better at avoiding HP receipt, selection toward HP tolerance strategies may be weaker and therefore the HP effects stronger when HP is deposited (Arceo‐Gómez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In flowering communities, heterospecific pollen (HP) transfer is common and can result in negative consequences for plant reproductive success such as reduced pollen tube growth and seed production [1][2][3][4][5][6]. HP transfer mainly occurs when various plant species share the same flower visitors [7], although wind-dispersed pollen and other random events may also play a role [3,8]. During foraging, insects often visit and collect pollen from flowers from multiple plant species and may consequently transfer con-and heterospecific pollen (CP / HP) to a stigma [9].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between floral traits, HP reception or donation and network properties are variable and even contradictory [3,26,27]. In general, stigma size, flower symmetry and floral size increase the likelihood and intensity of HP reception [3,27,28]. Short styles have been suggested to increase or decrease HP susceptibility [1,4,27].…”
Section: Introductionmentioning
confidence: 99%
“…With this study, we have contributed to the growing body of literature that uses molecular methods to understand pollen use by bees (Mitchell et al 2009, Galimberti 2014, Bell et al 2017, Galliot et al 2017, Lucas et al 2018, Bell et al 2019), and in the process provided some evidence for heterospecific pollen transfer in flowering plant communities (Mitchell et al 2009, Arceo-Gómez et al 2019a, b). That said, pollen balls in our study were typically comprised of only one species of Clarkia , which indicates that heterospecific pollen transfer may not be as common in the Clarkia system as in other flowering plant systems.…”
Section: Discussionmentioning
confidence: 99%